The complexity of compliance—Diverse responses to octopus fishery closures in Zanzibar - Elizabeth Drury O'Neill; Tim M. Daw; MWAMBAO; Rosemarie N. Mwaipopo; Emilie Lindkvist (People and Nature, 2024)
Abstract Marine protected areas like periodic closures are increasingly used to improve both fisheries management and biodiversity conservation, and often secondarily, human well‐being. Yet rule breaking, whether formal regulations, or community‐agreed norms, continues to negate expected management and conservation outcomes, remaining a major challenge. Although compliance scholarship today is expanding beyond non‐economic explanations of (non)‐compliance behaviour, approaches and theory used fail to show the diversity of perceptions and dispositions that can underpin motivations. A deepening engagement with behavioural sciences like sociology, psychology or behavioural economics is increasingly recognized as key in tackling compliance issues in marine protected areas. In this paper, we contribute to such a strand of compliance scholarship by presenting the responses and positions to (non‐) compliance, rules/regulations and authorities of different people, for example, fishers, traders and others involved in an area‐based fishery management intervention in Zanzibar, Tanzania. We take a qualitative approach aligning with an interpretive research ethic to carry out story circles, photo‐elicitation tasks and focus groups at three sites enacting periodic octopus closures. Theory drawn from sociology, anthropology and cognitive sciences was used to interpret how participants justified were motivated by or dispositioned towards rules, rule makers and rule breakers. Generally, the area‐management intervention was supported by participants, signalling the potential for future compliance most commonly based on the recognition of a degraded marine ecosystem in need of protection. However, the diverse and dynamic responses by different livelihood groups (i.e. traders and fishers) indicated on which basis and through which logics compliance behaviour was condoned or legitimated. This type of insight can help managers gauge or anticipate the potential for non‐compliance in participatory approaches that can impact the health of marine ecosystems. Recommendations include providing discussion spaces for conservation participants' (not just fishermen or fishery organizations) own meanings to be understood and not assumed. Meanings which create and shape relations, actions and concepts in marine protected area processes and thus directly impact the uptake and sustainability of conservation interventions. Read the free Plain Language Summary for this article on the Journal blog.